Clinical Profile of Stroke in Relation to Glycemic Status of the Patients - Bajracharya, Sunny; Shrestha, Bhakta Dev; Shrestha, Samrat; Gorkhaly, Manen Prasad (Med Phoenix, 2022)
Introduction Stroke is the sudden death of brain cells that occurs due to lack of oxygen, caused by blockage of blood flow or rupture of an artery to the brain leading to permanent disability or death. Diabetes mellitus has been established as a major risk factor for stroke. However, this study was conducted to incorporate glycemic status and its correlation with severity of stroke. Materials and Methods A cross-sectional observational study was conducted in the Department of Internal medicine, Neurosurgery, Emergency and Endocrinology of Bir Hospital. Ethical clearance was granted by Institutional Review board of National academy of medical sciences. A total of 50 patients with stroke presented within 72 hours of symptoms of stroke was included in the study. Data was collected and stored in MS-EXCEL sheet and analyzed using SPSS. Results Among 50 patients with stroke enrolled for the purpose of this study, 54% had ischemic and 46% hemorrhagic stroke. Patient pool was predominantly 51-60 years of age. Majority of the patients were euglycemic, of these 56.67% suffered hemorrhagic stroke, while known diabetics predominantly suffered ischemic stroke. Euglycemic patients had CT lesion measuring 5-10mm compared to larger lesions of >10mm in known diabetics. Euglycemic patients had better outcome in contrast to newly diagnosed and known diabetics. Conclusion The study found that patients with higher glucose levels had increased severity of stroke. Increased morbidity was documented among known diabetics and newly diagnosed cases of DM in comparison to euglycemics and patients with stress hyperglycemia.